An insightful evaluation of professionalism among dentistry students - Syed Rashid Habib; Kamran Sattar; Tauseef Ahmad; Rana M. Barakah; Abdulaziz M. Alshehri; Abdulelah F. Andejani; Abdulrahman A. Almansour (Elsevier, 2021)
Purpose: The objective of this study was to explore the ambience of professionalism related to academic integrity among undergraduate dental students. Methodology: "Dundee Polyprofessionalism Inventory I: Academic Integrity" was used to collect responses from first-year to fifth-year dental students of the College of Dentistry, King Saud University (Response rate = 78%). The participants' responses (for 34 professionalism lapses) were recorded by using the Dundee Polyprofessionalism Inventory. Statistical analysis included descriptive statistics, Chi-square, and T-tests (P < 0.05). Results: The "Ignore" sanction was not opted for any of the 34 professionalism behaviors, and there was unanimous agreement between the participants in considering all 34 behavior statements to be "wrong". Male and female participants were found to opt for a similar sanction as the median for 16 statements (47%), whereas, for 18 statements (53%), their responses differed with a range of levels 0.5 to 1.5. Preclinical- and clinical-year student responses also showed similarities in their 11 statements (32.3%), and they did differ for 20 statements (58.8%). Interestingly, clinical year respondents were overall on the stricter side of recommending sanctions. Conclusions: For the majority of the dental students tested, there was a good understanding of the significance of some lapses of professionalism associated with academic integrity. Some of the disclosures in this study were substantially appreciable because none of the students selected "ignore" sanction for any of the survey statements. We found that using the Dundee Polyprofessionalism Inventory for learning and understanding academic professionalism among dental students is useful.